PENGARUH TINGKAT BUNGA DAN PENGHIMPUNAN DANA TERHADAP KREDIT PERBANKAN DI INDONESIA - Muhammad Teguh; Rosmiyati Chodijah; Nopi Rosyita (Department of Development Economics, Universitas Sriwijaya, 2004)
The Purpose of this research is to know theform of relation between credit interest rate. society fund and credit distribution. The data that has been used is secondary data and the secondary data taken from many resources included the data from Badon Pusat Statistik and Indonesian Bank. Kind of analysis that have been used is by using multiple regression model. From the calculation the writer got R2 with the value 0,393 with indicated that 39.3 percent of credit Distribution effected by credit interest rate. society funds. From the t-test and outher test we can conclude that credit interest rate are not significant with the credit distribution, and society funds are significant to the credit distribution. The disturbance of banking intermediation or more popular in term disintermediation of credit distribution is reflected by the low position of LDR national banking. The low position of LDR indicates the decrease of banking ability in distributing credit if it's compared to the banking ability in colleting.fundfrom society. Keywords: Credit Distribution, Society Fund, Credit Interest Rate